1993
DOI: 10.1016/s0006-3495(93)81070-1
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved fluorescence of the single tryptophan of Bacillus stearothermophilus phosphofructokinase

Abstract: The fluorescence of the single tryptophan in Bacillus stearothermophilus phosphofructokinase was characterized by steady-state and time-resolved techniques. The enzyme is a tetramer of identical subunits, which undergo a concerted allosteric transition. Time-resolved emission spectral data were fitted to discrete and distributed lifetime models. The fluorescence decay is a double exponential with lifetimes of 1.6 and 4.4 ns and relative amplitudes of 40 and 60%. The emission spectra of both components are iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 47 publications
(47 reference statements)
1
40
0
Order By: Relevance
“…For E. coli PFK, the interactions between substrates and effectors have been studied extensively in this manner (20)(21)(22). However, in the case of wild-type BsPFK, the single tryptophan is for the most part unresponsive to conformational changes induced by ligand binding (23). The only change in the fluorescence properties of wild-type BsPFK is a 10% decrease in the intensity upon the binding of the inhibitor PEP to the allosteric site (23).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…For E. coli PFK, the interactions between substrates and effectors have been studied extensively in this manner (20)(21)(22). However, in the case of wild-type BsPFK, the single tryptophan is for the most part unresponsive to conformational changes induced by ligand binding (23). The only change in the fluorescence properties of wild-type BsPFK is a 10% decrease in the intensity upon the binding of the inhibitor PEP to the allosteric site (23).…”
Section: Figmentioning
confidence: 99%
“…However, in the case of wild-type BsPFK, the single tryptophan is for the most part unresponsive to conformational changes induced by ligand binding (23). The only change in the fluorescence properties of wild-type BsPFK is a 10% decrease in the intensity upon the binding of the inhibitor PEP to the allosteric site (23). This change has proven to be sufficient, in wild type and in the E161A͞R162A mutant, to assess the coupling interactions between Fru-6-P and PEP by monitoring the change in intensity upon PEP binding as a function of Fru-6-P concentration.…”
Section: Figmentioning
confidence: 99%
“…The origin of the complex fluorescence kinetics of Trp in proteins was a subject of extensive debate during the last two decades. The most interesting interpretations are the rotamer model (Szabo and Rayner 1980; Petrich et al 1983; Kim et al 1993; Dahms and Szabo 1997) and the recently proposed energy transfer model (Bajzer and Prendergast 1993). Nevertheless, some points remain unclear.…”
mentioning
confidence: 99%
“…Many studies have attempted to uncover the source of increased thermal stability in thermophilic enzymes, but it appears that there is not a single molecular or thermodynamic explanation, although the added stability is generally evident at all temperatures [35]. In the case of BsPFK, Kim et al showed that the native tryptophan position is quite rigid [36]. Additional fluorescence studies using tryptophan-shifted mutants have revealed that a majority of the BsPFK structure is rigid [16, 37, 38].…”
Section: Discussionmentioning
confidence: 99%